MMP-19 deficiency causes aggravation of colitis due to defects in innate immune cell function - Brauer, R; Tureckova, J; Kanchev, I; Khoylou, M; Skarda, J; Prochazka, J; Spoutil, F; Beck, I M; Zbodakova, O; Kasparek, P; Korinek, V; Chalupsky, K; et al. (Mucosal immunology, 2016)
Matrix metalloproteinases (MMPs) are potential biomarkers for disease activity in inflammatory bowel disease (IBD). However, clinical trials targeting MMPs have not succeeded, likely due to poor understanding of the biological functions of individual MMPs. Here, we explore the role of MMP-19 in IBD pathology. Using a DSS-induced model of colitis, we show evidence for increased susceptibility of Mmp-19-deficient (Mmp-19(-/-)) mice to colitis. Absence of MMP-19 leads to significant disease progression, with reduced survival rates, severe tissue destruction, and elevated levels of pro-inflammatory modulators in the colon and plasma, and failure to resolve inflammation. There was a striking delay in neutrophil infiltration into the colon of Mmp-19(-/-) mice during the acute colitis, leading to persistent inflammation and poor recovery; this was rescued by reconstitution of irradiated Mmp-19(-/-) mice with wild-type bone marrow. Additionally, Mmp-19-deficient macrophages exhibited decreased migration in vivo and in vitro and the mucosal barrier appeared compromised. Finally, chemokine fractalkine (CX3CL1) was identified as a novel substrate of MMP-19, suggesting a link between insufficient processing of CX3CL1 and cell recruitment in the Mmp-19(-/-) mice. MMP-19 proves to be a critical factor in balanced host response to colonic pathogens, and for orchestrating appropriate innate immune response in colitis.
Keywords: infiltrace neutrofily; Colitis; Macrophages; makrofágy; Matrix Metalloproteinases, Secreted; lidé; Colon; myši; Chemokine CX3CL1; metaloproteinasy secernované do matrix; kolitida; Immunity, Innate; progrese nemoci; Disease Progression; cytokiny; idiopatické střevní záněty; Cytokines; Humans; Mice; kultivované buňky; Intestinal Mucosa; Animals; Inflammation Mediators; síran dextranu; zvířata; myši inbrední C57BL; Dextran Sulfate; pohyb buněk; Mice, Knockout; přirozená imunita; kolon; Inflammatory Bowel Diseases; Neutrophil Infiltration; střevní sliznice; Cells, Cultured; Cell Movement; mediátory zánětu; chemokin CX3CL1; Mice, Inbred C57BL; myši knockoutované